Misiologi di Era Digital: Implikasi Etis dan Moral dalam Penggunaan Teknologi - Lie, Romi (JURNAL KADESI, 2025)
The rapid development of technology in recent years has had a significant impact on the field of missiology. However, technology also raises a number of ethical and moral issues that need to be considered in its use for mission purposes. This article aims to analyze the ethical and moral implications of using technology in missiology and provide ethical and moral principles that can guide the use of technology in mission. The article uses a qualitative approach by conducting a literature review from several sources relevant to missiology and technology. Ethical and moral principles must be integrated into the use of technology for mission to avoid potential issues and produce positive results in mission efforts